A review on modified sugarcane bagasse biosorbent for removal of dyes. (April 2021) - Aruna,; Bagotia, Nisha; Sharma, Ashok Kumar; Kumar, Surender
Abstract: This review provides an important insight on using Sugarcane Bagasse (SB) biosorbent in raw and modified form for removal of dyes from wastewater. Various methods of activation and modification of SB like physical, chemical, biological, composite formation and grafting were explored. Beside this, effect of different optimization conditions like adsorbent dosage, initial dye concentration, pH, temperature and contact time on the adsorption process were studied. Also, regeneration of dye loaded SB, the challenges and perspectives for future researches on waste-derived adsorbents were studied. Graphical abstract: Image 1 Highlights: Sugarcane Bagasse biosorbents are very effective for the removal of hazardous dyes. Different methods were summarized for modification of Sugarcane Bagasse. Sugarcane Bagasse and its different modified forms have excellent potential for removal of dyes from wastewater.